(untitled) (Italiano LinguaDue, 2023)
I laboratori di scrittura dell’Università di Milano spesso mostrano come alcune/i apprendenti non riescano sempre a discriminare un testo espositivo da un testo argomentativo, producendo, di conseguenza, testi meramente espositivi in luogo dei saggi argomentativi attesi. Con l’ausilio di alcuni spunti offerti dal Volume Complementare, e considerate le possibili cause dei fraintendimenti menzionati, il presente contributo propone uno strumento per supportare lo/la studente/essa nel riconoscimento dello schema espositivo o argomentativo soggiacente, in testi autentici e non necessariamente prototipici. Topic or thesis? Mediation and mediation strategies as support for the recognition of argumentative texts The writing workshops at the University of Milan often show how some learners cannot always discriminate an expository text from an argumentative text, thus producing merely expository texts instead of the expected argumentative essays. With the help of some hints offered by the QCER-Companion Volume and considering the possible causes of the mentioned misunderstandings, this contribution proposes a tool to support the learner in recognising the underlying expository or argumentative scheme in authentic and not necessarily prototypical texts.